Peningkatan Kesehatan Masyarakat Melalui Konsumsi Raw Food Daun Kelor Moringa oleivera Di Desa Talangsuko Kecamatan Turen Kabupaten Malang - Yulianti, eny; Hakim, Abdul; Khoiroh, Lilik Miftahul; Fasya, Ahmad Ghanaim; Hanapi, Ahmad; Harini, Sri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This journal discusses a community service program focused on improving public health through the consumption of Moringa oleivera (Moringa) leaves in raw food form in Talangsuko Village, Turen Subdistrict, Malang Regency. The selection of Moringa leaves is based on their high nutritional content and the underutilization of their health benefits as herbal plants in the local community. The research method employed is Participation Action Research (PAR), emphasizing a participatory and collaborative approach involving existing community groups such as PKK, Nahdatul Ulama organizations including the Fatayat and Muslimat women's communities, and the Ansor youth community. The educational approach includes providing information about the benefits of Moringa leaves, training in proper consumption methods, and collecting health data before and after participation. The community is educated on the proper consumption of Moringa leaves as herbal plants, emphasizing small, uncooked, and regular intake. Food integrated into the activities includes salads or raw vegetables with each meal, as additives in fruit or vegetable juices, and as antioxidant-rich infused water. Visits are conducted bi-weekly for two months, with continued online support through WhatsApp groups. The research findings indicated a significant improvement in public health, manifested by the reduction of complaints such as joint pain, headaches, common colds, susceptibility to flu, tingling sensations, fatigue, digestive issues, and cholesterol.